Roadside opioid testing of drivers using oral fluid: the case of a country with a zero tolerance law, Spain - Inmaculada Fierro; Mónica Colás; Juan Carlos González-Luque; F. Javier Álvarez (BMC, 2017)
Abstract Background Opioids can impair psychomotor performance, and driving under the influence of opioids is associated with an increased risk of accidents. The goals of this study were i) to determine the prevalence of opioids (heroin, morphine, codeine, methadone and tramadol) in Spanish drivers and ii) to explore the presence of opioids, more specifically whether they are used alone or in combination with other drugs. Methods The 2008/9 DRUID database regarding Spain was used, which provided information on 3302 drivers. All drivers included in the study provided a saliva sample and mass-chromatographic analyses were carried out in all cases. To determine the prevalence, the sample was weighted according to traffic intensity. In the case of opioid use combinations, the sample was not weighted. The detection limit for each substance was considered a positive result. Results The prevalence of opioids in Spanish drivers was 1.8% (95% CI, 1.4-2.3). Polydrug detection was common (56.2%): of these, in two out of three cases, two opioids were detected and cocaine was also detected in 86% of the cases. The concentration (median [Q1-Q3] ng/ml) of the substances was low: methadone 1.71 [0.10-15.30], codeine 40.55 [2.10-120.77], 6-acetylmorphine 5.71 [1.53-84.05], and morphine 37.40 [2.84-200.00]. Morphine was always detected with 6-acetylmorphine (heroin use). Conclusions Driving under the influence of opioids is relatively infrequent, but polydrug use is common. Our study shows that 6 out of 10 drivers with methadone in their OF (likely in methadone maintenance programs) are using other substances. This should be taken into account by health professionals in order to properly inform patients about the added risks of mixing substances when driving.